1970
DOI: 10.1104/pp.46.2.250
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Wall Loosening and Elongation by Acid Solutions

Abstract: The ability of low pH and CO2 to induce rapid cell elongation and wall loosening in the Avena coleoptile has been examined with the use of a continuous growth-recording technique and an Instron extensometer, respectively. In particular, the properties of the response to hydrogen ions have been examined in detail and have been compared with the responses initiated by CO2 and auxin. The optimal pH for growth is about 3.0, and both the maximal growth rate and wall extensibility are similar to that produced by opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
208
1
3

Year Published

1975
1975
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(222 citation statements)
references
References 6 publications
10
208
1
3
Order By: Relevance
“…Several lines of evidence are consistent with this hypothesis (7,9,19,24), but published measurements of auxin-induced release of acid from tissue into an external bathing medium (3,10,11,18) have not shown that auxin stimulates H+ secretion quickly enough to account for the rapid response (17) of elongation to auxin. If the acid secretion theory is correct it must be demonstrable that following exposure to an auxin the pH in the cell wall space falls to an elongation-stimulating value by the time that observable elongation in response to auxin actually commences, i.e.…”
Section: Introductionmentioning
confidence: 50%
“…Several lines of evidence are consistent with this hypothesis (7,9,19,24), but published measurements of auxin-induced release of acid from tissue into an external bathing medium (3,10,11,18) have not shown that auxin stimulates H+ secretion quickly enough to account for the rapid response (17) of elongation to auxin. If the acid secretion theory is correct it must be demonstrable that following exposure to an auxin the pH in the cell wall space falls to an elongation-stimulating value by the time that observable elongation in response to auxin actually commences, i.e.…”
Section: Introductionmentioning
confidence: 50%
“…Since the distance between the transducer shaft and root tip was large (120 mm) and total displacement before resetting was small (2 mm) ment angle varied only between 00 and 1°so tha (14) Figure 3, acid-induced elongation was recorded for 160 min with no sign of a decline. Thus acid-H induced elongation in intact pea roots is much more long lived than in coleoptile or corn root segments in which growth rate begins to decline 15 to 30 min after initiation (6,13). Figure 3 To recorder also shows that the acid growth response in pea roots can be obtained repeatedly by alternating between pH 6.5 and 4 in the root medium (lower curve).…”
mentioning
confidence: 83%
“…The resultant acidification of the cell wall is thought to lead to wall loosening and accelerated growth (5,8,13,14).…”
Section: Introductionmentioning
confidence: 99%